Should we patent it or keep it a secret? The moderating role of proactive orientation in family versus non-family SMEs. (August 2021) - Gimenez-Fernandez, Elena M; Beukel, Karin; Tyler, Beverly B; Spielmann, Nathalie; Cerrato, Daniele; Discua Cruz, Allan F; Minciullo, Marco
We investigate how family and non-family small-and-medium size enterprises (SMEs) differ in their preference for patenting over secrecy as a means to protect value of intellectual property, and how proactive orientation moderates this relationship. Because secrecy carries more risks for spillover than patenting, we propose and provide evidence to suggest that family SMEs are more likely to use patents than secrecy relative to non-family SMEs as a mechanism to protect value. However, proactive orientation can weaken this relationship, since SMEs with a proactive orientation will avoid the disclosure of information required for patenting. Using a sample of 300 SMEs from four countries in the wine industry, we find support for our hypotheses and contribute to both the intellectual property (IP) and SME literatures by explaining how family SMEs relative to non-family SMEs protect the value of IP.